P-70 Developing a hospice research culture: lessons from a randomised trial with 11 organisations. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Walshe, Catherine; Dodd, Steven; Algorta, Guillermo Perez; Hill, Matthew; Ockenden, Nick; Payne, Sheila; Preston, Nancy
Abstract : Background: The Hospice UK report 'Research in palliative care' has led to an increase in hospices wanting to become more research active. However, to do this they often need a research project to catalyse this, and ideally support from palliative care research institutions. Aim: To report on the research experiences of 11 palliative care units who were partners in a randomised trial of befriending services Methods: A wait-list controlled trial with nested qualitative case studies investigating volunteer delivered befriending services across 11 sites. Patients (n = 195) were estimated to be in their last year of life and randomly allocated to receive the befriending intervention immediately or after a four week wait. We report on the skills developed by non-clinical hospice staff who were responsible for site trial management and informed consent procedures. Results: Training for this role included innovative face-to-face role play workshops, access to good clinical practice education, and virtual site visits to check procedural compliance and address concerns. Trial initiation issues included acknowledging site staff design concerns and involving them in developing the trial protocol, documentation and research procedures. Areas that required acknowledgement and response during the trial included providing support to address issues of informed consent and eligibility, understanding the impact of the 'wait' allocation on participants, staff and volunteers, and integrating volunteer management and feedback into trial procedures. At subsequent feedback sessions, staff moved from being research naive to research active making recommendations about the design of future studies. Conclusions: For most this was the first time they had been involved in research yet they embraced this and developed research skills for future studies. The trial acted as a catalyst for training of staff who were able to contribute to running a rigorous and ethical wait-list trial. Funded by the UK Cabinet Office.